The Proliferation of the Urban Microfinance and its Problems and Prospects in Bangladesh (Global Journal of Human-Social Science, 2018)
The goal of this article is to inspect the current status, problems and, prospects of urban microfinance in Bangladesh. This article employs the descriptive research methods based on secondary data. This paper Illustrates the present scenario of urban microfinance by using tables, graphs and the trend analysis. This paper finds that the urban microfinance in Bangladesh has been growing tremendously during the last decades. During the 2006-2017 period, the number of members within the urban microfinance program has increased by 110.69%. Besides the amount of loan amount disbursed in the urban microfinance program has increased by 110.54 % during the last four years (2014)(2015)(2016)(2017). Also, the rate of increases of the total net savings of the urban microfinance members (373.33%) was higher than the rate of increases of the total net savings of the rural microfinance members (152.36%) during the 2009-2017 period. The loan Interest rate varies in between 15% and 30%. With regards to recovering the loan amount, 95% of the microfinance institutions (MFIs) apply the flat interest rate while the remaining 5% of the MFIs use the declining method.
Keywords: urban microfinance; problems and prospects; bangladesh